Borderline Personality Disorder in a “Life History Theory” Perspective: Evidence for a Fast “Pace-of-Life-Syndrome” - Otto, Benjamin; Kokkelink, Lisa; Brüne, Martin (Frontiers in Psychology, 2021)
“Borderline Personality Disorder” (BPD) is associated with heightened risk for cardiovascular disease and other stress-associated somatic consequences, which is poorly understood in terms of causal mechanisms, such as childhood trauma. Here, we tested the hypothesis suggesting that BPD reflects a fast “Pace-of-Life-Syndrome” (PoLS). Ninety-five women (44 diagnosed with BPD) were recruited to examine psychological correlates of PoLS, including life history features, personality dimensions, aggressiveness, chronic stress, borderline symptom severity, childhood trauma, and allostatic load (AL). In line with expectations, BPD patients had significantly higher scores suggestive of a fast PoLS than controls, they were more aggressive, more burdened with chronic stress and were exposed to more severe childhood adversity. Childhood trauma predicted PoLS, which in turn predicted AL. The present study thus provides direct evidence of psychological and somatic traits associated with the fast end of the PoLS spectrum in females with BPD. Findings are discussed with regard to clinical implications.